NATIONAL PRESCHOOL STANDARD CURRICULUM (NPSC) IN MALAYSIA KINDERGARTEN- TEACHER'S RETROSPECTIVE - Mohd Nazri Bin Abdul Rahman; Jothy Letchummi Ganditasan (P3I UMSurabaya, 2024)
How Preschool Teachers feel about the National Preschool Standard Curriculum in Malaysia. This study takes a closer look at how two preschool teachers in the Klang Valley feel about the National Preschool Standard Curriculum (NPSC). We interviewed them to understand their experiences, challenges, and suggestions for improvement. While they appreciate the NPSC's focus on play and a well-rounded education, they also highlighted some difficulties. These include a lack of resources, large class sizes, and limited training opportunities. They also pointed out a gap between the curriculum's ideals and what's happening in the classroom. By understanding their perspectives, we hope to improve the implementation of the NPSC and enhance the learning experience for young children in Malaysia. They recommended improved training programs, higher resource allocation, and a stronger emphasis on matching assessment methodologies with the NPSC's developmental goals. These findings highlight the importance of increased teacher assistance in maximizing the curriculum's influence on early childhood education in Malaysia. The study provides valuable views on the continuing discourse on NPSC.